Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1063/1.3517448
|View full text |Cite
|
Sign up to set email alerts
|

Motion of cancer-cell lamellipodia perturbed by laser light of two wavelengths

Abstract: We employ 405 and 1064 nm laser light to perturb the motions of lung cancer cell lamellipodia. The 405 nm light causes lamellipodial retractions while the 1064 nm light enhances protrusions. With the observation of actin distributions in the lamellipodia, we find that the 1064 nm laser light increases the density of actin near the illuminated site, while the 405 nm light reduces the actin distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Biener et al found that the polarization of light could apply torques on the actin filaments in cells and hence influenced the motility of neuroblastoma cells, which tended to align along the direction of polarization of the electric field [5]. Using a two-wavelength setup, Xiao et al verified that focused laser light spots can be used to influence the growth and retraction of cellular lamellipodia [6]. Recently, spatial light modulators (SLMs) have been employed to facilitate a variety of cellular guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Biener et al found that the polarization of light could apply torques on the actin filaments in cells and hence influenced the motility of neuroblastoma cells, which tended to align along the direction of polarization of the electric field [5]. Using a two-wavelength setup, Xiao et al verified that focused laser light spots can be used to influence the growth and retraction of cellular lamellipodia [6]. Recently, spatial light modulators (SLMs) have been employed to facilitate a variety of cellular guidance.…”
Section: Introductionmentioning
confidence: 99%
“…This study of cell size, providing a three-dimensional view, was performed using an optimized optical profilometry (Schmidt and Black, 1992; Chen et al, 2009; Xiao et al, 2010; Zouani et al, 2012; Pan et al, 2011; Lei et al, 2013) and a specific cell treatment protocol, which allowed for a vertical nanometer resolution. Other features that are characteristic of a mature osteoblast include (i) an increase in Runx2 and Col-I expression and (ii) an increase in ECM (osteoid-like matrix) production.…”
Section: Introductionmentioning
confidence: 99%
“…This wavelength was selected for the compromise between high optical effects on perturbing the cell movements and low phototoxicity in comparison with the 405 nm light used in our previous work. 10 Because the shape and size of an optical pattern remained the same within a propagation distance longer than 20 μm, the optical patterns actually formed light walls around the adherent cells. Under suitable intensity and contrast of the optical pattern, the cells continued proliferating to fill up the region enclosed by the light walls.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually difficult to vary the culture patterns during experiments. In contrast, using laser light to pattern cell growth, 7,8 to influence the directions of cell migration, 9,10 or to detach and re-orientate adherent cells, 11 is dynamic and accurate in both spatial and temporal domains. In addition, a number of research groups have demonstrated arbitrary patterning of floating cells by using optoelectronic tweezers.…”
Section: Introductionmentioning
confidence: 99%